UNLAWFUL ACTS RESULTING IN CRIMINAL PENALTIES IN GOVERNMENT PROCUREMENT OF GOODS AND SERVICES BASED ON DECISION NO.10/PID.SUS-TPK/2021PN BNA - Fariq Abiyyu Nawar; Mohammad Eka Putra; Mulhadi (PT. Radja Intercontinental Publishing, 2025)
Corruption case No. 10/Pid.Sus-TPK/2021/PN Bna, this case is quite interesting because it itself explains how a tendering process for the procurement of goods/services by the government which turns out to have many irregularities and conspiracies in it which actually also aims to benefit and enrich oneself by harming the state's finances. The research methods used in this study are normative with analytical descriptive properties, the approach used is normative and case approaches, data sources used are secondary data, techniques and data collection tools for literature studies, qualitative data analysis with deductive and inductive conclusions drawn. The results of the study stated that the Regulation regarding the procurement of goods and services according to Presidential Regulation Number 12 of 2021 concerning the Procurement of Government Goods and Services provides guidelines for the Regulation, to the procedures for the Procurement of Government Goods and Services that are Simple, Clear, and Comprehensive in accordance with good governance. It is carried out in 3 stages, namely: Unlawful acts in the procurement of goods and services can be subject to criminal sanctions are acts that abuse authority and arbitrariness. Abuse of authority and arbitrariness is basically a teaching of state administrative law, in the law on the eradication of corruption (PTPK Law), namely Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 explains the abuse of authority, namely in the provisions of article 3. Consideration of the Panel of Judges on Unlawful Acts that resulted in Criminal Offense in case no. 10/Pid.Sus-TPK/2021/PN Bna That the defendant was the head of the Simeuelue Regency PUPR office and as a budget user in road and bridge maintenance activities at the Simeulue Regency PUPR office in 2017.